Adaptation of the Rumination About an Interpersonal Offense Scale into Turkish - Tuncay Oral; Coskun Arslan (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
The aim of the study is to adapt Rumination about an Interpersonal Offense Scale (RIO) developed by Wade, Vogel, Liao and Goldman (2008) into Turkish on a group university students. 450 students and 55 English teacher candidates from Pamukkale University participated in the study. The English and Turkish version of the scale were administered to teacher candidates in English language teaching to test the linguistic equivalence of the scale. Significant positive correlation (r=.77) between English and Turkish version scores were found. The results of confirmatory factor analysis demonstrated that this scale yielded one factor, as original form (x2/sd=3,82, p [JCBPR 2017; 6(3.000): 101-107]